Analysis the Impact of the Forest Crisis on Merauke Women in the Perspective of Ecofeminism - Meyland Wambrauw; Ketsia Ohee; Apriani Anastasia (Jurnal Perempuan dan Anak, 2022)
Forests are the most important part of human survival, including the people in Merauke Regency, Papua. The benefits of forests for Papuans are felt directly as a source of life, as pharmacies that provide natural medicines. Forests also provide all human needs that can be used for free. For Papuans, the forest has a philosophical affinity for women. In the 2001-2019 period, forest destruction in Merauke was the highest in Papua Province. Therefore, this study aims to examine the impact of the forest crisis on women in Merauke. This research also intends to examine the process of the forest crisis, as well as the efforts made by the government and other related institutions in dealing with these problems. By using qualitative methods and secondary data sourced from relevant books, articles, and web pages on the website, the author tries to analyze the topic using ecofeminism theory and the concept of human security. The results and conclusions obtained from this study are that the forest crisis in Merauke is on average caused by the opening of plantations dominated by oil palm. The impact on indigenous peoples, which includes women, is oppression, violations of the rights of indigenous peoples, an increasingly heavy double burden to the threat of poverty, hunger and disease. In this case, government policies are considered not optimal to overcome these problems.